PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING PADA MATERI HAK DAN KEWAJIBAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI KELAS XII-2 SMA NEGERI 1 RANTAU SELATAN - Safira, Aulia (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Learning motivation arises due to intrinsic factors, which include the desire and will to succeed, as well as the drive for learning needs. The extrinsic factors are the recognition of a conducive, comfortable, and interesting learning environment. In essence, learning motivation is both an internal and external drive in students with supporting indicators. This type of drive plays a significant role in a person’s success in learning. Based on the observation results related to the decreasing learning motivation of students in class XII-2 at SMA Negeri 1 Rantau Selatan in the subject of Pancasila Education, a classroom action research was conducted using the Role Playing learning model with the topic of rights and obligations as citizens in a short drama. The classroom action research was carried out in two cycles, referring to the Kemmis Taggart Model. Based on the data analysis, a questionnaire score of 900 was obtained. This score indicates that the students' learning motivation is in the high category. When the data was presented as percentages, the result in cycle II was 80.16%, showing an improvement compared to the data in cycle I, which was 65.20%. By applying the rights and obligations for the nation’s generation, Indonesia's national goal of fostering a just and democratic life will be realized.